Protective Effect of Unacylated Ghrelin on Compression-Induced Skeletal Muscle Injury Mediated by SIRT1-Signaling - Ugwu, Felix N.; Yu, Angus P.; Sin, Thomas K.; Tam, Bjorn T.; Lai, Christopher W.; Wong, S. C.; Siu, Parco M. (Frontiers in Physiology, 2017)
Unacylated ghrelin, the predominant form of circulating ghrelin, protects myotubes from cell death, which is a known attribute of pressure ulcers. In this study, we investigated whether unacylated ghrelin protects skeletal muscle from pressure-induced deep tissue injury by abolishing necroptosis and apoptosis signaling and whether these effects were mediated by SIRT1 pathway. Fifteen adult Sprague Dawley rats were assigned to receive saline or unacylated ghrelin with or without EX527 (a SIRT1 inhibitor). Animals underwent two 6-hour compression cycles with 100 mmHg static pressure applied over the mid-tibialis region of the right limb whereas the left uncompressed limb served as the intra-animal control. Muscle tissues underneath the compression region, and at the similar region of the opposite uncompressed limb, were collected for analysis. Unacylated ghrelin attenuated the compression-induced muscle pathohistological alterations including rounding contour of myofibers, extensive nucleus accumulation in the interstitial space, and increased interstitial space. Unacylated ghrelin abolished the increase in necroptosis proteins including RIP1 and RIP3 and attenuated the elevation of apoptotic proteins including p53, Bax and AIF in the compressed muscle. Furthermore, unacylated ghrelin opposed the compression-induced phosphorylation and acetylation of p65 subunit of NF-kB. The anti-apoptotic effect of unacylated ghrelin was shown by a decrease in apoptotic DNA fragmentation and terminal dUTP nick-end labelling index in the compressed muscle. The protective effects of unacylated ghrelin vanished when co-treated with EX527. Our findings demonstrated that unacylated ghrelin protected skeletal muscle from compression-induced injury. The myoprotective effects of unacylated ghrelin on pressure-induced tissue injury were associated with SIRT1 signaling.